La teoría de la regulación: aportes para comprender las dinámicas de desarrollo económico y crisis en el capitalismo industrial del siglo XX - Emilia Ormaechea; Joel Sidler; Julieta Almada (Revista Iberoamericana de Estudios de Desarrollo)
In this article, it is systematized the conceptual framework of the French School of Regulation, in order to analyze the dynamics of development and crisis that took place since the late nineteenth century and during the twentieth century in the industrialized capitalist economies. Particularly, the configuration of the «golden years of capitalism» is explained by addressing the transition from an extensive accumulation regime to an intensive one, as well as by analyzing the shift from the competitive to monopolistic mode of regulation. Finally, the inherent contradictions within the monopolistic-intensive mode of development are exposed, which affected the previous institutional stability and gave rise to a new crisis of capitalism towards the 1970s.